Celebrating Organization Theory: The After‐Party. (15th July 2014) - Davis, Gerald F.
Abstract Organization and management theory as a field faces criticisms from several scholars that it has an unhealthy obsession with 'theory', while at the same time seeing very little cumulative theoretical progress. Some have even accused the field of being mired in the 1970s. Lounsbury and Beckman counter with an expansive review of several thriving domains of contemporary organizational research that demonstrate the theoretical vibrancy of the field. This article responds by seeking to define 'theoretical progress' in ways that extend beyond just the volume of articles produced. It finds that 1970s‐era classics have seen a surge of citations since the turn of the twenty‐first century, consistent with a view of limited progress. It concludes by outlining three areas of problem‐driven research eminently worthy of attention from organizational researchers.